Lean Accounting System: Importance and Successful Implementation - ALI, SYED BABAR; KHAN, ZEBA SHARIFF; SHAH, ZUBAIR A; AHMAD, MUHAMMAD (The journal of contemporary issues in business and government, 2021)
A lean accounting system is a complex phenomenon the success of which can depend on several factors. Efforts to implement and/or maintain a successful lean accounting system have failed many times, however, only a few studies have addressed this predicament of the implementers. The objective of this study is to find out the importance of lean accounting system, and the reasons behind its successful implementation. A thorough literature review was performed to meet the research questions.It was found that a successful lean accounting system requires continual strong commitment from top management, introduction of congruent accounting methods,existence of a lean manufacturing/operational system, and effective collaboration with value-stream teams.This study has contributed to extant research by unearthing the interrelationship among the variables such as manufacturing system, traditional accounting system, lean accounting system, role of top management, and others to find out the ingredients of a successful lean accounting implementation.